2015
DOI: 10.1016/j.drugpo.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of image and performance enhancement drug use in a male British South Asian community

Abstract: The study is intended to contribute to health policy and practice debate around the targeting of dedicated education, outreach and harm reduction for ethnic groups engaged in IPED use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 78 publications
(65 reference statements)
2
26
1
2
Order By: Relevance
“…Even if we were to hypothesise that prevalence among recreational users in the Middle East was similar, how this influences the upward trend in IPED injecting observed at Australian NSPs remains unclear. Van Hout and Kean's qualitative interviews with 20 South‐Asian IPED users in Northern England found that some participants had been introduced to IPEDs in their countries of origin . However, our study found no evidence that MENA or other CALD participants were any more likely than Anglo‐Australian participants to have ever injected IPEDs overseas nor were they more likely to have imported IPEDs.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Even if we were to hypothesise that prevalence among recreational users in the Middle East was similar, how this influences the upward trend in IPED injecting observed at Australian NSPs remains unclear. Van Hout and Kean's qualitative interviews with 20 South‐Asian IPED users in Northern England found that some participants had been introduced to IPEDs in their countries of origin . However, our study found no evidence that MENA or other CALD participants were any more likely than Anglo‐Australian participants to have ever injected IPEDs overseas nor were they more likely to have imported IPEDs.…”
Section: Discussioncontrasting
confidence: 81%
“…Research from the USA, Scandinavia, UK and other European countries dominates, although emerging evidence from sub‐Saharan Africa , Latin America and the Middle East suggests that IPED prevalence in these regions may also be significant. Very little research to date has explored IPED use among cultural and ethnic diasporas . An increase in harms associated with IPED injecting has the potential to exacerbate health inequalities .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, we do not have participant profile in terms of their citizenship or religiosity. Van Hout and Kean (2015) reported that male Muslim users of AAS and other IPEDs in the UK felt these substances led them to be in control of and promoted their perceptions of their physical and spiritual health, and were not harmful, thus circumventing religious parameters. In addition, we recognise that use of AAS in Islamic faith is discouraged and the legality of AAS is unclear in some Eastern Mediterranean countries where regulatory controls are complex and varied.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados pueden deberse a la ilegalidad del uso de esteroides en el deporte sin receta médica. Es difícil establecer la prevalencia exacta de uso porque las personas que las usan lo hacen de manera clandestina, la mayoría de las veces sin receta médica, y adquiriendo los EAA en el mercado negro (Coomber et al, 2014;Pope et al, 2000;Van Hout y Kean, 2015).…”
Section: Discussionunclassified
“…Estos métodos artificiales se basan en el uso de esteroides anabolizantes androgénicos (EAA) (Kanayama, Barry, Hudson, y Pope, 2006). Son "sustancias de la imagen corporal", como los llaman Kanayama et al (2006), porque no se usan por su acción psicoactiva, sino por su efecto sobre la imagen corporal (Coomber et al, 2014;Van Hout y Kean, 2015) por parte de las personas afectadas por DM (Rohman, 2009). Por sus efectos secundarios nocivos para la salud del deportista, estas sustancias exógenas son ilegales en el deporte sin receta médica.…”
unclassified